Method for accurately measuring components of multi-element silicon-based alloy
Through the combined use of multi-step sample pretreatment and multiple detection methods, the interference problem in the determination of multi-silicon-based alloy components is solved, and the accurate determination of Si, Cr, Ce, Al and C elements is realized, and the SiC single crystal substrate is supported. efficient growth and resolution of solvents.
Patent Information
- Application Number
- CN202411461842.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2024-12-20
AI Technical Summary
It is difficult to accurately determine the composition of polysilicon-based alloys in the prior art, especially in the co-solvent system containing Si, Cr and rare earth elements. There are interference and dissolution problems in element determination, which affects the growth law of SiC single crystal substrate and co-solvent recovery.
Multi-step sample pretreatment methods, including microwave digestion, acid dissolution treatment and reduction titration, combined with the combination of inductively coupled plasma atomic emission spectrometer and infrared carbon sulfur analyzer, eliminate interference between elements and accurately determine Si, Cr, and Ce , content of Al and C elements.
The precise determination of the components of polysilicon-based alloys is achieved, which reduces the experimental cycle and improves the reliability and repeatability of the measurement data. It has important application significance for the growth of SiC single crystal substrates and the recycle of solvents.
Smart Images

Figure CN119165109A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the application field of accurate determination of elemental composition of multinary silicon-based alloy samples, and specifically involves the design of a multinary silicon-based alloy acid dissolution system, the elimination of interference factors in the determination of different elements, and a method for accurately determining the composition of multinary silicon-based alloys by the combined use of different detection instruments. Background Art
[0002] In order to alleviate the energy security issues facing the world, power electronic devices are currently developing in the direction of high frequency, integration, standard modularization and intelligence. The physical limit bottleneck of traditional silicon-based devices is becoming increasingly prominent, and it is difficult to adapt to the more complex electronic and electrical architecture requirements of future terminal applications. In contrast, the third-generation semiconductor materials represented by silicon carbide (SiC) have the advantages of wide band gap, high breakdown field strength, high thermal conductivity, high electron mobility and strong radiation resistance. They can effectively break through the limitations of key material performance indicators and significantly improve device performance. They have both strategic and market characteristics. After decades of development, SiC semiconductor materials have become the preferred material for high-temperature, high-frequency, high-voltage and high-power power electronic devices and radio frequency microwave devices, and are regarded as an important support for the core competitiveness of the country's new generation of information technology.
[0003] The design and development of SiC devices rely on high-quality single crystal substrates. Currently, commercial SiC single crystal substrates are mainly grown using physical vapor transport (PVT), which has defects such as high defect concentration of SiC substrate wafers and backward p-type substrate wafer preparation technology. Since the liquid phase method is closer to the thermodynamic equilibrium state, it can produce larger and better quality crystals when preparing SiC crystals, effectively overcoming the limitations of PVT, and has therefore received widespread attention in recent years. During the liquid phase growth process, the addition of a co-solvent is used to reduce the growth temperature of SiC, so that the crystal growth process is carried out within a relatively low temperature range. This method can not only increase the growth rate, but also improve the quality of the crystal, while achieving efficient growth of p-type crystals.
[0004] The selection of solvent in top seed solution growth (TSSG) is very important. The ideal solvent system should have the characteristics of strong carbon solubility, high carbon supersaturation, strong stability, low cost and environmental friendliness. Based on the precise measurement technology of solvent composition, it can not only provide experimental support for the calculation of phase diagram of multi-solvent system by establishing the concentration field of solvent system, but also specify the solvent recovery plan according to the measured results, thereby greatly reducing the design and feeding cost of solvent, which is of great significance to the large-scale production of high-quality single crystal substrates and the development of related fields.
[0005] The acid leaching method (using acid such as concentrated hydrochloric acid, sulfuric acid, etc.) in the common silica ore component detection is difficult to solve the dissolution problem in the silicon-based alloy component detection, especially the current multi-component silicon-based alloy as a solvent for the growth of SiC single crystals by the liquid phase method. The accurate detection scheme of its chemical composition is still imperfect, especially for the chemical composition detection means of the commonly used solvent system containing Si, Cr and other rare earth elements (such as Ce, etc.) still needs to be developed. The main difficulty in accurately determining the composition of this type of silicon-based alloy material is: when determining the Si element, the hydrofluoric acid used to dissolve the sample will react with the Ce element to form a precipitate. If sodium hydroxide is used to dissolve the Si element, the Cr element cannot be dissolved. Therefore, the pretreatment methods of the above two samples cannot solve the problem of the difficulty of dissolving the component alloy, which seriously affects the use of the instrument. In addition, different sample pretreatment schemes and determination methods are designed for different elements, and the mutual interference between the determination of different elements is also to be solved. Therefore, the development of new sample pretreatment methods and multi-element efficient and accurate component determination methods is very important for analyzing the growth law of SiC single crystals in different solvent systems, and it is also an urgent problem to design solvent recovery routes. Summary of the invention
[0006] The present invention discloses a method for accurately determining the composition of a multi-component silicon-based alloy to solve any of the above and other potential problems in the prior art.
[0007] In order to solve the above technical problems, the present invention provides a technical solution: a method for accurately determining the composition of a multi-component silicon-based alloy, the method specifically comprising the following steps:
[0008] S1) grinding the multi-component silicon-based alloy to be tested, and dividing it into three equal parts after sieving to obtain a test sample;
[0009] S2) mixing one of the test samples with a certain amount of the first acid solvent, digesting it with microwaves to obtain a clear solution, and then taking out a portion of the clear solution for heating and oxidation to obtain an oxidized clear solution;
[0010] S3) mixing another test sample with a certain amount of the second acid solvent, filtering to obtain a filtrate and a filter residue after acid dissolution treatment, performing alkali melting and slag recovery treatment on the filter residue to obtain a leachate, and then mixing the leachate with the filtrate;
[0011] S4) performing reduction titration on the oxidized clear solution obtained in S2) to obtain the Cr element content;
[0012] The unoxidized clarified solution obtained in S2) and the mixed solution of the filtrate and the leaching solution obtained in S3) are measured for Si, Ce and Al element contents using an inductively coupled plasma atomic emission spectrometer;
[0013] The third test sample was tested using an infrared carbon-sulfur analyzer to determine the C element content, ultimately obtaining the precise composition content of the multi-component silicon-based alloy.
[0014] Further, the multi-component silicon-based alloy in S1) is a silicon-chromium alloy;
[0015] The mesh number of the sieve is 120 meshes.
[0016] Further, the specific process parameters of the microwave digestion in S2) are:
[0017] S2.1) First, 0.0450 g to 0.0550 g of the test sample is mixed with 13 mL to 15 mL of the first acid solvent and placed in a microwave digestion tank;
[0018] S2.2) Raise the temperature to 115-125°C at 12°C / min and keep warm for 30-50min; then raise the temperature to 200-210°C at 9°C / min and keep warm for 60-80min; then turn off the heating and cool naturally to room temperature to obtain a clear solution;
[0019] S2.3) Remove the clear solution obtained after microwave digestion, add 15mL-25mL of sulfur-phosphorus mixed acid, and heat on a hot plate until a large amount of white smoke emerges. After cooling to room temperature, dilute the solution to 100mL-150mL, and then add 15mL-20mL of oxidant and 1mL-3mL of catalyst respectively. Place the solution on a hot plate and heat until large bubbles emerge. Slowly add 5mL-10mL of 1% sodium chloride solution, place the solution on the hot plate again and heat until large bubbles emerge, and stop heating.
[0020] Furthermore, the first acid solvent in S2.1) is a mixture of nitric acid, hydrofluoric acid and sulfuric acid in a volume ratio of (4-6):(4-6):(2-3).
[0021] Further, in said S2.3), the oxidant is a 20% ammonium persulfate solution; the catalyst is a 1% silver nitrate solution;
[0022] Sulfur-phosphorus mixed acid is prepared by mixing 30% sulfuric acid and 30% phosphoric acid in equal volumes.
[0023] Further, the specific process of the electric heating plate heating acid dissolution treatment in S3) is:
[0024] S3.1) Weigh 0.0450 g to 0.0550 g of the test sample and 23 mL to 25 mL of the second acid solvent respectively, and set aside; first add the nitric acid and hydrofluoric acid in the second acid solvent into a tetrafluoroethylene beaker, then add the test sample, and heat until the sample powder is dissolved;
[0025] S3.2) After cooling to room temperature, add perchloric acid and heat until smoke appears until the solution is concentrated to 1 mL-2 mL. After cooling slightly, add concentrated hydrochloric acid and 3-5 drops of hydrogen peroxide, and filter to obtain a filtrate and a residue;
[0026] S3.3) subjecting the filter residue obtained in S3.2) to alkali melting to obtain a leachate, and mixing the leachate with the filtrate obtained in S3.2) to obtain a mixture of the filtrate and the leachate.
[0027] Furthermore, the second acid solvent in S3.1) includes nitric acid, hydrofluoric acid, perchloric acid and concentrated hydrochloric acid, and the volume ratio of nitric acid, hydrofluoric acid, perchloric acid and concentrated hydrochloric acid is: (4-6): (4-6): (2-3): (9-11).
[0028] Further, the specific process of alkali melting slag treatment in S3.3) is:
[0029] Wrap it with filter paper and place it in a platinum crucible. After ashing in a muffle furnace for 1h-1.5h, add 2g-2.5g of mixed flux, heat and melt it in a muffle furnace for 10min-15min, and then place it in a dilute hydrochloric acid solution to dissolve it to obtain a leachate.
[0030] Further, the mixed solvent includes anhydrous sodium carbonate and boric acid, and the mass ratio between the two is (6-8):(2-4);
[0031] The dilute hydrochloric acid solution is a mixture of concentrated hydrochloric acid and pure water in a volume ratio of 1:8.
[0032] Furthermore, the reduction titration process is to add 2-3 drops of sodium diphenylamine sulfonate indicator to the heated oxidized solution, and after shaking, the solution turns purple. A 2% ammonium ferrous sulfate solution is used for redox titration, and the titration endpoint is when the solution color changes from purple to green.
[0033] The present invention has the following advantages and more excellent characteristics:
[0034] 1) Good sample dissolution effect, fast dissolution speed, short experimental cycle and high operability;
[0035] 2) The mutual interference factors in the determination process of each element in the sample are eliminated to the greatest extent, especially the interference between the determination of Si element and Ce element by using hydrofluoric acid to dissolve;
[0036] 3) The measured data are of great application significance for finding the carbon solubility law of different solvent systems in the TSSG method for growing SiC, predicting the growth of new systems, and realizing the recycling of remaining solvents. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1The present invention is a flowchart of a method for accurately determining the composition of a multi-component silicon-based alloy material.
[0038] Figure 2 Schematic diagram of relative standard deviation of Cr element detection data in Example 1 of the present invention.
[0039] Figure 3 Schematic diagram of relative standard deviation of Si element detection data in Example 1 of the present invention.
[0040] Figure 4 Schematic diagram of relative standard deviation of Ce element detection data in Example 1 of the present invention.
[0041] Figure 5 Schematic diagram of relative standard deviation of Al element detection data in Example 1 of the present invention.
[0042] Figure 6 Schematic diagram of relative standard deviation of C element detection data in Example 1 of the present invention.
[0043] Figure 7 Schematic diagram of relative standard deviation of Cr element detection data in Example 2 of the present invention.
[0044] Figure 8 Schematic diagram of relative standard deviation of Si element detection data in Example 2 of the present invention.
[0045] Fig. 9 Schematic diagram of relative standard deviation of Ce element detection data in Example 2 of the present invention.
[0046] Fig.10 Schematic diagram of relative standard deviation of C element detection data in Example 2 of the present invention.
[0047] Fig.11 Schematic diagram of relative standard deviation of Si element detection data in Example 3 of the present invention.
[0048] Fig.12 Schematic diagram of relative standard deviation of Ce element detection data in Example 3 of the present invention.
[0049] Fig.13 Schematic diagram of relative standard deviation of C element detection data in Example 3 of the present invention. DETAILED DESCRIPTION
[0050] In order to better describe the present invention, the present invention is further described in detail below in conjunction with examples. The following content is illustrative rather than restrictive, and the embodiments of the present invention are not limited thereto.
[0051] like Figure 1As shown, the present invention provides a method for accurately determining the composition of a multi-component silicon-based alloy, and the method specifically comprises the following steps:
[0052] S1) grinding the multi-component silicon-based alloy to be tested, and dividing it into three equal parts after sieving to obtain a test sample;
[0053] S2) mixing one of the test samples with a certain amount of the first acid solvent, digesting it with microwaves to obtain a clear solution, and then taking out a portion of the clear solution for heating and oxidation to obtain an oxidized clear solution;
[0054] S3) mixing another test sample with a certain amount of the second acid solvent, filtering to obtain a filtrate and a filter residue after acid dissolution treatment, performing alkali melting and slag recovery treatment on the filter residue to obtain a leachate, and then mixing the leachate with the filtrate;
[0055] S4) performing reduction titration on the oxidized clear solution obtained in S2) to obtain the Cr element content;
[0056] The unoxidized clarified solution obtained in S2) and the mixed solution of the filtrate and the leaching solution obtained in S3) are measured for Si, Ce and Al element contents using an inductively coupled plasma atomic emission spectrometer;
[0057] The third test sample was tested using an infrared carbon-sulfur analyzer to determine the C element content, ultimately obtaining the precise composition content of the multi-component silicon-based alloy.
[0058] Further, the sample described in S1) comes from the residual flux after SiC is grown by TSSG method, which is a silicon-chromium alloy with a certain amount of carbon dissolved therein, and the chemical components contained include but are not limited to elements such as Si, Cr, Ce, Al, and C;
[0059] The reaction containers are respectively a special reaction container for microwave digestion instrument and a polytetrafluoroethylene beaker;
[0060] The added mass of the sample is related to the measuring range of the instrument, and the sample weighing amount is 0.0450g-0.0550g.
[0061] Further, the acid solvent described in S2) is one or a mixture of hydrofluoric acid, nitric acid, sulfuric acid, perchloric acid, and concentrated hydrochloric acid;
[0062] The mass fraction of the hydrofluoric acid used to prepare the acid solvent is 40%; the mass fraction of the nitric acid is 65%; the mass fraction of the sulfuric acid is 98%; the mass fraction of the perchloric acid is 70%; and the mass fraction of the concentrated hydrochloric acid is 37%.
[0063] The specific ratio of acid solvent mixed with the powder sample in the microwave digestion tank is nitric acid, hydrofluoric acid and sulfuric acid, and the volume ratio is (4-6): (4-6): (2-3). The total volume of the acid solvent can be adjusted according to the specific sample, and the total volume can be 13mL-15mL;
[0064] The microwave digestion apparatus heating program is:
[0065] Set the heating program, heat to 115-125℃ at 12℃ / min, keep warm for 30-50min; then heat to 200-210℃ at 9℃ / min, keep warm for 60-80min; then turn off the heating and cool naturally to room temperature.
[0066] The specific process of acid dissolution by electric heating plate is as follows:
[0067] After adding nitric acid and hydrofluoric acid in a set ratio to a polytetrafluoroethylene beaker, heat until the sample powder dissolves. After cooling slightly, add perchloric acid and heat until smoke appears until the solution is concentrated and 1mL-2mL remains. After cooling slightly, add concentrated hydrochloric acid and 3-5 drops of hydrogen peroxide and heat until the sample powder is basically dissolved.
[0068] The specific ratio of acid solvent mixed with the powder sample in the polytetrafluoroethylene beaker is nitric acid, hydrofluoric acid, perchloric acid and concentrated hydrochloric acid, and the volume ratio is (4-6):(4-6):(2-3):(9-11); the total volume of the acid solvent can be adjusted according to the specific sample, and the total volume can be 23mL-25mL;
[0069] Furthermore, the mass fraction of the hydrogen peroxide used is 30%.
[0070] Further, the filtrate and filter residue described in S2) are obtained by filtering the solution obtained after heating and dissolving on a hot plate;
[0071] The alkali melting slag recovery process is:
[0072] The filter residue wrapped with quantitative filter paper is placed in a platinum crucible, and after ashing in a muffle furnace for 1h-1.5h, 2g-2.5g of anhydrous sodium carbonate and boric acid mixed flux is added, and after heating and melting in a muffle furnace for 10min-15min, it is placed in a dilute hydrochloric acid solution to dissolve to obtain a leachate.
[0073] The mass ratio of the anhydrous sodium carbonate and the boric acid mixed flux is (6-8):(2-4);
[0074] The dilute hydrochloric acid solution is a mixture of concentrated hydrochloric acid and pure water in a volume ratio of 1:8.
[0075] Further, the specific method of instrument detection of the components in S3) is:
[0076] The sample powder can be directly measured for carbon content using an infrared carbon-sulfur analyzer, and the measurement is repeated three times in parallel, and the results are averaged;
[0077] The clear solution obtained after the microwave digestion can be diluted and fixed to volume, and the Si element content can be determined using an inductively coupled plasma atomic emission spectrometer;
[0078] The filtrate obtained after acid dissolution and filtration is heated by the electric heating plate, and mixed with the leachate obtained after alkali melting and slag recovery. The obtained mixed solution is diluted and fixed to volume, and the Ce and Al element contents can be determined using an inductively coupled plasma atomic emission spectrometer;
[0079] The redox titration process is:
[0080] Remove the clear solution obtained after microwave digestion, add 15mL-25mL sulfuric acid (30% sulfuric acid and 30% phosphoric acid mixed in equal volumes) and heat on a hot plate until a lot of white smoke comes out. After cooling slightly, dilute the solution to 100mL-150mL, then add 15mL-20mL 20% ammonium persulfate solution and 1mL-3mL 1% silver nitrate solution respectively, place the solution on a hot plate and heat until large bubbles come out, then slowly add 5mL-10mL 1% sodium chloride solution, place the solution on the hot plate again and heat until large bubbles come out, then stop heating.
[0081] Add 2-3 drops of sodium diphenylamine sulfonate indicator to the heated oxidized solution and shake until the solution turns purple. Record the volume of ammonium ferrous sulfate before titration. 1, Use 2% ammonium ferrous sulfate solution for redox titration. The end point of titration is when the solution color changes from purple to green. Record the volume V2 of ammonium ferrous sulfate at the end point of titration.
[0082] According to the formula Calculate the chromium content in the sample.
[0083] In the formula, C is the concentration of ammonium ferrous sulfate; V2 is the volume of ammonium ferrous sulfate at the titration endpoint, mL; V1 is the volume of ammonium ferrous sulfate before titration, mL; m is the weight of the sample in the microwave digestion tank, g; M is the relative atomic mass of chromium, g / mol, 51.996 g / mol.
[0084] The above detection method can be used to accurately determine the content of each element in the silicon-chromium alloy that serves as the residual flux after SiC crystal growth.
[0085] Embodiment 1:
[0086] The samples tested in this embodiment were provided by the Institute of Physics, Chinese Academy of Sciences and Beijing Crystal Grid Semiconductor Co., Ltd. The elements in the co-solvent include Si, Cr, Ce, Al and C. Due to patents involved, the proportion of raw materials and the determination are not described in the present invention.
[0087] Take a sample of the co-solvent, grind it into powder, and pass it through a 120-mesh sieve for later use.
[0088] Weigh 0.0500g (accurate to 0.0050g) of sample powder into a microwave digestion tank, add 5mL nitric acid, 5mL hydrofluoric acid and 3mL concentrated sulfuric acid in sequence, assemble the microwave digestion tank, place it in a microwave digestion instrument, set the heating program, heat to 120℃ at 12℃ / min, and keep warm for 30min; then heat to 210℃ at 9℃ / min, and keep warm for 70min; then turn off the heating, cool naturally to room temperature and then take out, wash the microwave digestion tank several times with a small amount of deionized water, transfer the washing liquid and the clarified solution after digestion to a polytetrafluoroethylene beaker, and dilute the mixed solution to 250mL for standby use.
[0089] Use a pipette to accurately transfer 50mL of the diluted clear solution, add 20mL of sulfuric acid (30% sulfuric acid and 30% phosphoric acid mixed in equal volumes), and heat on a hot plate until a lot of white smoke comes out. After cooling slightly, add deionized water to dilute to 100mL, then add 20mL of 20% ammonium persulfate solution and 2mL of 1% silver nitrate solution respectively, heat until large bubbles appear in the solution, slowly add 5mL of 1% sodium chloride solution, heat again until the solution appears large bubbles, stop heating, add 2 drops of sodium diphenylamine sulfonate indicator, shake thoroughly, and change the color of the solution from orange-yellow to purple. Use 2% ammonium ferrous sulfate solution for reduction titration, and the titration end point is when the solution color changes from purple to green.
[0090] According to the formula Calculate the chromium content in the sample.
[0091] In the formula, C is the concentration of ammonium ferrous sulfate; V2 is the volume of ammonium ferrous sulfate at the titration endpoint, mL; V1 is the volume of ammonium ferrous sulfate before titration, mL; m is the weight of the sample in the microwave digestion tank, g; M is the relative atomic mass of chromium, g / mol, 51.996 g / mol.
[0092] The titration was performed three times in parallel and the results were averaged.
[0093] The remaining clear solution was measured for Si content using an inductively coupled plasma atomic emission spectrometer. The measurement was repeated three times and the results were averaged.
[0094] Weigh 0.0500g (accurate to 0.0050g) of sample powder in a polytetrafluoroethylene beaker, add 5mL nitric acid and 5mL hydrofluoric acid respectively, and heat on a hot plate until the sample powder is dissolved. After cooling slightly, add 3mL perchloric acid and heat until a large amount of white smoke comes out, and the solution is about 1mL and removed. After cooling slightly, add 10mL concentrated hydrochloric acid and 3 drops of 30% hydrogen peroxide, and heat until the sample powder is basically completely dissolved. After removing and cooling, use quantitative filter paper to filter to obtain filtrate and filter residue, place the filter residue wrapped in quantitative filter paper in a platinum crucible, heat on a hot plate to fully dry, place in a muffle furnace, ash at 800℃ for 1h, take out and cool, use 2g anhydrous sodium carbonate and boric acid mixed flux (the mass ratio of anhydrous sodium carbonate to boric acid is 7:3) to cover the slag, melt at 800℃ in a muffle furnace for 10min, cool and dissolve in 5% dilute hydrochloric acid to obtain a leachate. The filtrate was mixed with the leaching solution and diluted to 250 mL, and the Ce and Al content in the solution was determined using an inductively coupled plasma atomic emission spectrometer. The determination was repeated three times and the results were averaged.
[0095] Weigh 0.2g of sample powder and place it in a ceramic crucible with 0.6g of iron filings in advance, add 0.5g of tin particles, and then add 1.5g of tungsten particles to cover the entire sample. Put the ceramic crucible into an infrared carbon-sulfur analyzer to determine the C content in the sample powder. Perform three parallel measurements and take the average value of the results.
[0096] The relative standard deviations (RSDs) of the results for the determined Cr, Si, Ce, Al and C elements were 0.36%, 0.87%, 2.59%, 3.14% and 1.51%, respectively (see Figure 2 , Figure 3 , Figure 4 , Figure 5 and Figure 6 ), indicating that the method for determining the composition of the multi-element silicon-based alloy material designed in the present invention has good repeatability. In addition, the sum of the results obtained by different determination methods for each element is 99.95%, reflecting the reliability of the determination method in the present invention.
[0097] Embodiment 2:
[0098] The samples tested in this embodiment were provided by the Institute of Physics, Chinese Academy of Sciences and Beijing Crystal Grid Semiconductor Co., Ltd. The elements in the co-solvent include Si, Cr, Ce and C. Due to patents involved, the proportion of raw materials and the determination are not described in the present invention.
[0099] Take a sample of the co-solvent, grind it into powder, and pass it through a 120-mesh sieve for later use.
[0100] Weigh 0.0500g (accurate to 0.0050g) of sample powder into a microwave digestion tank, add 5mL nitric acid, 5mL hydrofluoric acid and 3mL concentrated sulfuric acid in sequence, assemble the microwave digestion tank, place it in a microwave digestion instrument, set the heating program, heat to 120℃ at 12℃ / min, and keep warm for 30min; then heat to 210℃ at 9℃ / min, and keep warm for 70min; then turn off the heating, cool naturally to room temperature and then take out, wash the microwave digestion tank several times with a small amount of deionized water, transfer the washing liquid and the clarified solution after digestion to a polytetrafluoroethylene beaker, and dilute the mixed solution to 250mL for standby use.
[0101] Use a pipette to accurately transfer 50mL of the diluted clear solution, add 20mL of sulfuric acid (30% sulfuric acid and 30% phosphoric acid mixed in equal volumes), and heat on a hot plate until a lot of white smoke comes out. After cooling slightly, add deionized water to dilute to 100mL, then add 20mL of 20% ammonium persulfate solution and 2mL of 1% silver nitrate solution respectively, heat until large bubbles appear in the solution, slowly add 5mL of 1% sodium chloride solution, heat again until the solution appears large bubbles, stop heating, add 2 drops of sodium diphenylamine sulfonate indicator, shake thoroughly, and change the color of the solution from orange-yellow to purple. Use 2% ammonium ferrous sulfate solution for reduction titration, and the titration end point is when the solution color changes from purple to green.
[0102] According to the formula Calculate the chromium content in the sample.
[0103] In the formula, C is the concentration of ammonium ferrous sulfate; V2 is the volume of ammonium ferrous sulfate at the titration endpoint, mL; V1 is the volume of ammonium ferrous sulfate before titration, mL; m is the weight of the sample in the microwave digestion tank, g; M is the relative atomic mass of chromium, g / mol, 51.996 g / mol.
[0104] The titration was performed three times in parallel and the results were averaged.
[0105] Weigh 0.0500g (accurate to 0.0050g) of sample powder in a polytetrafluoroethylene beaker, add 5mL nitric acid and 5mL hydrofluoric acid respectively, and heat on a hot plate until the sample powder is dissolved. After cooling slightly, add 3mL perchloric acid and heat until a large amount of white smoke comes out, and the solution is about 1mL and removed. After cooling slightly, add 10mL concentrated hydrochloric acid and 3 drops of 30% hydrogen peroxide, and heat until the sample powder is basically completely dissolved. After removing and cooling, use quantitative filter paper to filter to obtain filtrate and filter residue, place the filter residue wrapped in quantitative filter paper in a platinum crucible, heat on a hot plate to fully dry, place in a muffle furnace, ash at 800℃ for 1h, take out and cool, use 2g anhydrous sodium carbonate and boric acid mixed flux (the mass ratio of anhydrous sodium carbonate to boric acid is 7:3) to cover the slag, melt at 800℃ in a muffle furnace for 10min, cool and dissolve in 5% dilute hydrochloric acid to obtain a leachate. The filtrate was mixed with the leaching solution and diluted to 250 mL, and the Ce content in the solution was determined using an inductively coupled plasma atomic emission spectrometer. The determination was repeated three times and the results were averaged.
[0106] Weigh 0.2g of sample powder and place it in a ceramic crucible with 0.6g of iron filings in advance, add 0.5g of tin particles, and then add 1.5g of tungsten particles to cover the entire sample. Put the ceramic crucible into an infrared carbon-sulfur analyzer to determine the C content in the sample powder. Perform three parallel measurements and take the average value of the results.
[0107] The relative standard deviations (RSDs) of the results of the determined Cr, Si, Ce and C elements were 2.08%, 1.41%, 2.37%, 3.63% respectively (see Figure 7 , Figure 8 , Fig. 9 and Fig.10 ), indicating that the method for determining the composition of the multi-element silicon-based alloy material designed in the present invention has good repeatability. In addition, the sum of the results obtained by different determination methods for each element is 99.85%, reflecting the reliability of the determination method in the present invention.
[0108] Embodiment three:
[0109] The samples tested in this embodiment were provided by the School of Chemistry and Bioengineering of University of Science and Technology Beijing, and the elements in the samples included Si, Ce and C.
[0110] Take a sample of the co-solvent, grind it into powder, and pass it through a 120-mesh sieve for later use.
[0111] Weigh 0.0500g (accurate to 0.0050g) of sample powder in a microwave digestion tank, add 5mL nitric acid, 5mL hydrofluoric acid and 3mL concentrated sulfuric acid in order, assemble the microwave digestion tank, place it in a microwave digestion instrument, set the heating program, heat to 120℃ at 12℃ / min, keep warm for 30min; then heat to 210℃ at 9℃ / min, keep warm for 70min; then turn off the heating, cool naturally to room temperature and take it out, wash the microwave digestion tank several times with a small amount of deionized water, transfer the washing liquid and the clarified solution after digestion to a polytetrafluoroethylene beaker, dilute the mixed solution to 250mL, and use an inductively coupled plasma atomic emission spectrometer to determine the Si element content in the solution. Parallel determination was performed 3 times, and the results were averaged.
[0112] Weigh 0.0500g (accurate to 0.0050g) of sample powder in a polytetrafluoroethylene beaker, add 5mL nitric acid and 5mL hydrofluoric acid respectively, and heat on a hot plate until the sample powder is dissolved. After cooling slightly, add 3mL perchloric acid and heat until a large amount of white smoke comes out, and the solution is about 1mL and removed. After cooling slightly, add 10mL concentrated hydrochloric acid and 3 drops of 30% hydrogen peroxide, and heat until the sample powder is basically completely dissolved. After removing and cooling, use quantitative filter paper to filter to obtain filtrate and filter residue, place the filter residue wrapped in quantitative filter paper in a platinum crucible, heat on a hot plate to fully dry, place in a muffle furnace, ash at 800℃ for 1h, take out and cool, use 2g anhydrous sodium carbonate and boric acid mixed flux (the mass ratio of anhydrous sodium carbonate to boric acid is 7:3) to cover the slag, melt at 800℃ in a muffle furnace for 10min, cool and dissolve in 5% dilute hydrochloric acid to obtain a leachate. The filtrate was mixed with the leaching solution and diluted to 250 mL, and the Ce content in the solution was determined using an inductively coupled plasma atomic emission spectrometer. The determination was repeated three times and the results were averaged.
[0113] Weigh 0.05g of sample powder and place it in a ceramic crucible with 0.6g of iron filings in advance, add 0.5g of tin particles, and then add 1.5g of tungsten particles to cover the entire sample. Put the ceramic crucible into an infrared carbon-sulfur analyzer to determine the C content in the sample powder. Perform three parallel measurements and take the average value of the results.
[0114] The relative standard deviations (RSDs) of the determined results for Si, Ce and C were 0.65%, 0.47% and 3.73%, respectively (see Fig.10 , Fig.11 and Fig.12 ), indicating that the silicon-chromium alloy composition determination method designed in the present invention has good repeatability. In addition, the sum of the results of each element obtained by different determination methods is 100.01%, reflecting the reliability of the determination method in the present invention.
[0115] The above is a detailed introduction to a method for accurately determining the composition of a multi-component silicon-based alloy provided in the embodiment of the present application. The description of the above embodiment is only used to help understand the method and its core idea of the present application; at the same time, for those skilled in the art, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
[0116] For example, certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that hardware manufacturers may use different nouns to refer to the same component. This specification and claims do not use differences in names as a way to distinguish components, but use differences in the functions of components as the criteria for distinction. As mentioned throughout the specification and claims, "including" and "comprising" are open-ended terms, so they should be interpreted as "including / including but not limited to". "Approximately" means that within an acceptable error range, those skilled in the art can solve the technical problem within a certain error range and basically achieve the technical effect. The subsequent description of the specification is a preferred embodiment of the present application, but the description is for the purpose of illustrating the general principles of the present application, and is not used to limit the scope of the present application. The scope of protection of the present application shall be determined by the definition of the attached claims.
[0117] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0118] The above description shows and describes several preferred embodiments of the present application, but as mentioned above, it should be understood that the present application is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the application concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not deviate from the spirit and scope of the present application, and should be within the scope of protection of the claims attached to the present application.
Claims
1. A method for accurately determining the composition of multi-component silicon-based alloys. It is characterized in that The determination method specifically comprises the following steps: S1) grinding the multi-component silicon-based alloy to be tested, and dividing it into three equal parts after sieving to obtain a test sample; S2) mixing one of the test samples with a certain amount of the first acid solvent, digesting it with microwaves to obtain a clear solution, and then taking out a portion of the clear solution for heating and oxidation to obtain an oxidized clear solution; S3) mixing another test sample with a certain amount of the second acid solvent, filtering to obtain a filtrate and a filter residue after acid dissolution treatment, performing alkali melting and slag recovery treatment on the filter residue to obtain a leachate, and then mixing the leachate with the filtrate; S4) performing reduction titration on the oxidized clear solution obtained in S2) to obtain the Cr element content; The unoxidized clarified solution obtained in S2) and the mixed solution of the filtrate and the leaching solution obtained in S3) are measured for Si, Ce and Al element contents using an inductively coupled plasma atomic emission spectrometer; The third test sample was tested using an infrared carbon-sulfur analyzer to determine the C element content, ultimately obtaining the precise composition content of the multi-component silicon-based alloy.
2. The assay method according to claim 1, It is characterized in that The multi-component silicon-based alloy in S1) is a silicon-chromium alloy; The mesh number of the sieve is 120 meshes.
3. The assay method according to claim 1, It is characterized in that The specific process parameters of the microwave digestion in S2) are: S2.1) First, 0.0450 g to 0.0550 g of the test sample is mixed with 13 mL to 15 mL of the first acid solvent and placed in a microwave digestion tank; S2.2) Raise the temperature to 115-125°C at 12°C / min and keep warm for 30-50min; then raise the temperature to 200-210°C at 9°C / min and keep warm for 60-80min; then turn off the heating and cool naturally to room temperature to obtain a clear solution; S2.3) Remove the clear solution obtained after microwave digestion, add 15mL-25mL of sulfur-phosphorus mixed acid, and heat on a hot plate until a large amount of white smoke emerges. After cooling to room temperature, dilute the solution to 100mL-150mL, and then add 15mL-20mL of oxidant and 1mL-3mL of catalyst respectively. Place the solution on a hot plate and heat until large bubbles emerge. Slowly add 5mL-10mL of 1% sodium chloride solution, place the solution on the hot plate again and heat until large bubbles emerge, and stop heating.
4. The assay method according to claim 3, It is characterized in that The first acid solvent in S2.1) is a mixture of nitric acid, hydrofluoric acid and sulfuric acid in a volume ratio of (4-6):(4-6):(2-3).
5. The assay method according to claim 3, It is characterized in that In said S2.3), the oxidant is a 20% ammonium persulfate solution; the catalyst is a 1% silver nitrate solution; Sulfur-phosphorus mixed acid is prepared by mixing 30% sulfuric acid and 30% phosphoric acid in equal volumes.
6. The assay method according to claim 1, It is characterized in that The specific process of the acid dissolution treatment by heating on the electric heating plate in S3) is as follows: S3.1) Weigh 0.0450 g to 0.0550 g of the test sample and 23 mL to 25 mL of the second acid solvent respectively, and set aside; first add the nitric acid and hydrofluoric acid in the second acid solvent into a tetrafluoroethylene beaker, then add the test sample, and heat until the sample powder is dissolved; S3.2) After cooling to room temperature, add perchloric acid and heat until smoke appears until the solution is concentrated to 1 mL-2 mL. After cooling slightly, add concentrated hydrochloric acid and 3-5 drops of hydrogen peroxide, and filter to obtain a filtrate and a residue; S3.3) subjecting the filter residue obtained in S3.2) to alkali melting to obtain a leachate, and mixing the leachate with the filtrate obtained in S3.2) to obtain a mixture of the filtrate and the leachate.
7. The assay method according to claim 6, It is characterized in that The second acid solvent in S3.1) includes nitric acid, hydrofluoric acid, perchloric acid and concentrated hydrochloric acid, and the volume ratio of nitric acid, hydrofluoric acid, perchloric acid and concentrated hydrochloric acid is: (4-6): (4-6): (2-3): (9-11).
8. The assay method according to claim 6, It is characterized in that The specific process of alkali melting slag treatment in S3.3) is as follows: Wrap it with filter paper and place it in a platinum crucible. After ashing in a muffle furnace for 1h-1.5h, add 2g-2.5g of mixed flux, heat and melt it in a muffle furnace for 10min-15min, and then place it in a dilute hydrochloric acid solution to dissolve it to obtain a leachate.
9. The assay method according to claim 8, It is characterized in that The mixed solvent includes anhydrous sodium carbonate and boric acid, and the mass ratio between the two is (6-8):(2-4); The dilute hydrochloric acid solution is a mixture of concentrated hydrochloric acid and pure water in a volume ratio of 1:
8.
10. The measuring method according to claim 1, It is characterized in that The reduction titration process is to add 2-3 drops of sodium diphenylamine sulfonate indicator to the heated oxidized solution, and after shaking, the solution turns purple. A 2% ammonium ferrous sulfate solution is used for redox titration, and the titration end point is when the solution color changes from purple to green.
